Transcylindrical Cholecystectomy for the Treatment of Cholelithiasis and Its Complications Cholecystectomy Under Local Anesthesia - Talens, E. Javier Grau; Cattáneo, Julio Horacio; Rubio, Rafael Giraldo; Castro, Pablo Gustavo Mangione (IntechOpen, 2011)
None